Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1029/2001gb001398
|View full text |Cite
|
Sign up to set email alerts
|

Cutover peatlands: A persistent source of atmospheric CO2

Abstract: [1] Peatlands represent an important component of the global carbon cycle, storing 23 g C m À2 yr À1 . Peatland mining eliminates the carbon sink function of the peatland. In this paper we measure the total ecosystem respiration in a natural, 2 and 3 year (young) and 7 and 8 year (old) postcutover peatland near Sainte-Marguerite-Marie, Québec, during the summers of 1998 and 1999. Although the natural site was a source of CO 2 during the dry 1998 study season (138 g C m À2 ), CO 2 emissions were between 260 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
2
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 202 publications
(96 citation statements)
references
References 32 publications
4
86
2
1
Order By: Relevance
“…The 10th and 90th percentile are indicated by the bars, the 25th and 75th percentiles with the top and bottom of the box and the median value by the centre line. (Data for Canada and Fennoscandia taken from the following studies; Tuittila and Komulainen, 1995;Sundh et al, 2000;Waddington et al, 2002;Glatzel et al, 2003;McNeil and Waddington, 2003;Tuittila et al, 2004;Cleary et al, 2005;Alm et al, 2007a;Shurpali et al, 2008;Waddington et al, 2010;Järveoja et al, 2012;Mander et al, 2012;Salm et al, 2012;Strack et al, 2014. ) Where studies reported seasonal fluxes (typically May to October), these were converted to annual fluxes by assuming that 15 % of the flux occurs in the nongrowing season soil moisture (Lindsay et al, 2014.…”
Section: Effects Of Climatementioning
confidence: 99%
See 1 more Smart Citation
“…The 10th and 90th percentile are indicated by the bars, the 25th and 75th percentiles with the top and bottom of the box and the median value by the centre line. (Data for Canada and Fennoscandia taken from the following studies; Tuittila and Komulainen, 1995;Sundh et al, 2000;Waddington et al, 2002;Glatzel et al, 2003;McNeil and Waddington, 2003;Tuittila et al, 2004;Cleary et al, 2005;Alm et al, 2007a;Shurpali et al, 2008;Waddington et al, 2010;Järveoja et al, 2012;Mander et al, 2012;Salm et al, 2012;Strack et al, 2014. ) Where studies reported seasonal fluxes (typically May to October), these were converted to annual fluxes by assuming that 15 % of the flux occurs in the nongrowing season soil moisture (Lindsay et al, 2014.…”
Section: Effects Of Climatementioning
confidence: 99%
“…Annual CO 2 -C emissions (in tonnes of CO 2 -C yr −1 ) from peatlands managed for extraction in the ROI and UK calculated using the IPCC 2006 Good Practice Guidance (Tier 1 value: 0.2 and 1.1 t CO 2 -C ha −1 yr −1 for nutrient-poor and nutrient-rich peatlands respectively), the IPCC 2013 Wetlands Supplement (Tier 1 value: 2.8 t CO 2 -C ha −1 yr −1 ) and the Emission Factors derived in this study (Table 2). Areas (ha) and CO 2 -C emissions using the IPCC 2006 Good Practice Guidance values are taken from the 2014 National Inventory Reports (NIR) for the ROI (Duffy et al, 2014) and the UK (Webb et al, 2014 this should provide an impetus for the rewetting of highly emitting land use categories such as peatlands managed for extraction, particularly as these areas will remain persistent long-term emission hotspots in the absence of rewetting actions (Waddington et al, 2002).…”
Section: Implications For National Inventory Reportingmentioning
confidence: 99%
“…However, restoring the hydrology of a cutover peatland can be very expensive due to the costs of implementing the various restoration techniques, and is often delayed until many years after abandonment. Consequently, this leads to a large and persistent source of atmospheric CO 2 due to the decomposing peat and the unvegetated surface (Waddington et al, 2002). The restored peatland hydrology does not resemble that of a natural peatland within the first few years post restoration (Shantz and Price, 2005), and it has been suggested that this will not occur until an acrotelm (upper peat layer) is established on the cutover peatland surface (Shantz and Price, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…During this abandoned stage, the water table position in the now cutover peatland becomes more variable. Volumetric moisture content (VMC) of the peat is lowered and soil-water tension increases (Price, 1996), leading to an increase in peat decomposition (Waddington et al, 2002) and low vegetation productivity (Greenwood, 2005). As soil moisture and soil water tension decrease, water is held more tightly within small pores of decomposed peat, limiting water availability to plants, especially nonvascular peat forming Sphagnum mosses (Price and Whitehead, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…CO2 emissions from drained peatlands can increase by 100%-400% when compared to pristine peatlands due to drainage and removal of vegetation [16]. However, CH4 emissions are subsequently reduced due to the reduction in the anoxic zone and the absence of peatland vegetation which can easily be degraded [17].…”
Section: Disturbed Peatlandsmentioning
confidence: 99%